2016
DOI: 10.1083/jcb.201511080
|View full text |Cite
|
Sign up to set email alerts
|

A noncatalytic function of the topoisomerase II CTD in Aurora B recruitment to inner centromeres during mitosis

Abstract: The C-terminal domain (CTD) of Topo II is dispensable for its catalytic activity yet essential for Topo II function in chromosome segregation during mitosis. Here, Edgerton et al. resolve the role of the Topo II CTD during mitosis in yeast, showing that it functions noncatalytically via the Haspin-H3 T3-Phos pathway to recruit Ipl1/Aurora B to mitotic inner centromeres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 64 publications
1
54
0
3
Order By: Relevance
“…One highly conserved SUMO substrate is Topoisomerase II (or Top2) (Clarke and Azuma, 2017). Sumoylation of Top2 C-terminal non-catalytic region leads to centromeric recruitment of Top2 itself to decatenate intertwined DNA before anaphase, as well as other mitotic factors (Claspin, Haspin and Aurora B kinases) to promote centromeric segregation (Azuma et al, 2003; Bachant et al, 2002; Dawlaty et al, 2008; Edgerton et al, 2016; Ryu et al, 2010; Ryu et al, 2015a). The SUMO pathway also affects centromeric histones and other mitotic regulators (Mukhopadhyay and Dasso, 2017).…”
Section: Sumo Modulates Chromosome Structures and Functionsmentioning
confidence: 99%
“…One highly conserved SUMO substrate is Topoisomerase II (or Top2) (Clarke and Azuma, 2017). Sumoylation of Top2 C-terminal non-catalytic region leads to centromeric recruitment of Top2 itself to decatenate intertwined DNA before anaphase, as well as other mitotic factors (Claspin, Haspin and Aurora B kinases) to promote centromeric segregation (Azuma et al, 2003; Bachant et al, 2002; Dawlaty et al, 2008; Edgerton et al, 2016; Ryu et al, 2010; Ryu et al, 2015a). The SUMO pathway also affects centromeric histones and other mitotic regulators (Mukhopadhyay and Dasso, 2017).…”
Section: Sumo Modulates Chromosome Structures and Functionsmentioning
confidence: 99%
“…See also Fig EV5. ª In Xenopus egg extracts and budding yeast (Edgerton et al, 2016;Yoshida et al, 2016), the CTD of TOP2A (Topo II in yeast) has been shown to interact with Haspin, the kinase responsible for histone H3 Thr-3 phosphorylation (H3pT3) in mitosis (Dai et al, 2005). Scale bars, 10 lm.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies in Xenopus and yeast showed that SUMOylated DNA topoisomerase IIα Cterminal domain can bind Haspin and regulate its localization at centromeres [34,35] (Figure 3). …”
Section: How Is Haspin Recruited Onto Chromosomes?mentioning
confidence: 99%